2005
DOI: 10.1136/jcp.2004.019349
|View full text |Cite
|
Sign up to set email alerts
|

Transformed dermatofibrosarcoma protuberans: a clinicopathological study of eight cases

Abstract: Background: Fibrosarcomatous (FS) or malignant fibrous histiocytomatous (MFH) transformation of dermatofibrosarcoma protuberans (DFSP) is a rare, but well known, entity. DFSPs with sarcomatous areas have questionable biological behaviour. Several studies suggest that they have a higher risk for local recurrence and distant metastases than ordinary DFSPs. One recent study described no difference in the behaviour of conventional and transformed DFSP. Aims: To investigate the biological behaviour of a series of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 17 publications
0
42
1
3
Order By: Relevance
“…The cells in these areas usually show higher cellularity, increased mitotic rate, a focal loss of CD34 in 50% of cases (Mentzel et al 1998;Szollosi and Nemes 2005;Abbott et al 2006), and a marked nuclear pleomorphism to normal DFSP tissue. Sarcomatous change of DFSP is a form of tumor progression and is associated with a worse prognosis than ordinary DFSP (Mentzel et al 1998;Szollosi and Nemes 2005).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…The cells in these areas usually show higher cellularity, increased mitotic rate, a focal loss of CD34 in 50% of cases (Mentzel et al 1998;Szollosi and Nemes 2005;Abbott et al 2006), and a marked nuclear pleomorphism to normal DFSP tissue. Sarcomatous change of DFSP is a form of tumor progression and is associated with a worse prognosis than ordinary DFSP (Mentzel et al 1998;Szollosi and Nemes 2005).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 97%
“…They are the "classic" form of DFSP. Rarely, DFSP can transform into Wbrosarcomatous DFSP (FS-DFSP), a more aggressive tumor, characterized clinically by a higher metastatic potential (Wrotnowski et al 1988;Ding et al 1989;Connelly and Evans 1992;Mentzel et al 1998;Bowne et al 2000;Fiore et al 2005;Szollosi and Nemes 2005). It may require a more intensive treatment approach.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Histologically, dermatofibrosarcoma protuberans with fibrosarcomatous areas shows higher proliferative activity (higher mitotic rate or MIB-1 labeling index) than ordinary dermatofibrosarcoma protuberans. 23,29,30 Since no correlation was observed between the mRNA expression level of PDGFB/PDGFRB and the histologic subtype, the fibrosarcomatous transformation of dermatofibrosarcoma protuberans is thought to be caused by mechanisms such as the TP53 gene mutation 29,31 or microsatellite instability 31 rather than the generation of the fusion gene and the activation of its downstream PDGFRB signaling pathway.…”
Section: Pdgfb and Pdgfrb Mrna Expressionmentioning
confidence: 99%
“…A review of the literature published in 1996 found a mean recurrence rate of 18% (range, 0-60%) after treatment with wide local excision in 15 studies by DuBay D et al (2004). Szollosi Z et al (2005) mentioned that distant metastasis (1 % -4%) and tumour related deaths are extremely rare. Re-excision of tumour positive areas until tumour-free margins are obtained or 'histographical surgery' ensures a high cure rate of up to 97% while preserving normal tissue as mentioned by Park T.H et al (2011).…”
Section: Discussionmentioning
confidence: 99%